PENGARUH VARIASI LAJU ALIR UDARA DAN FILTER TERHADAP PROSES GASIFIKASI DENGAN SISTEM DOWNDRAFT - Syarif, Aida (KINETIKA, 2020)
Coal gasification is the process of converting solid into a gas mixture that has fuel value. Coal gasification will produce gas in the form of synthetic gas (syngas) with the main components consisting of carbon monoxide (CO), hydrogen (H2), and (CH4) gas. By converting coal using gasification as a clean energy producer, a blower as a regulator of air flow, cyclones as a tar separator and a gas cooler. The results of this study are the rate of fuel use, the rate of burning ash, the specific gestation rate, the specific gas production rate, the syngas flow rate, the flash point calorific value, and the efficiency of the classification process. The decrease in the combustion air flow rate will tend to make the combustion temperature and the calorific value become smaller so that the efficiency will also decrease. The best efficiency occurs at the largest airflow rate of 3.15 m/s with an efficiency of 84.62%.The increase in the mass of the husk that is filtered will cause an increase in the composition of CH4 and H2, as well as a decrease in CO2 and CO. By filtering the mass of rice husks, the LHV value will increase.